To Rosario, Dead from Abuse - Llaguno, Jenny (Review of Women's Studies; Vol 4 No 1 (1994): Review of Women's Studies Volume IV, Number 1 (1993-1994), 1995)
Translated by Jenny Llaguno from the original "Kay Rosario na Namatay sa Isang Pang-aabuso" by Ruby Palma Beltran.